2001
DOI: 10.1046/j.1444-2906.2001.00241.x
|View full text |Cite
|
Sign up to set email alerts
|

Models for forecasting sandfish catch in the coastal waters off Akita Prefecture and the evaluation of the effect of a 3-year fishery closure

Abstract: SUMMARY: The sandfish Arctoscopus japonicus in the coastal waters off Akita Prefecture had been landed in amounts of more than 10 000 t continuously from 1963 to 1975. From 1976, however, it began to decrease sharply and fell to only 74 t in 1984. The fishery society of Akita Prefecture closed the fishing from 1 September 1992 to 30 September 1995. Since 1995, the total allowable catch (TAC) allocated in each year has increased. However, the mechanism behind the increment of catch has not been clearly demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 1 publication
3
14
0
Order By: Relevance
“…The relationship between catch and SST obtained and the methodology used here are very similar to those obtained by Sakuramoto et al. , 18,19 Oh et al. , 9 and Watanabe 21 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The relationship between catch and SST obtained and the methodology used here are very similar to those obtained by Sakuramoto et al. , 18,19 Oh et al. , 9 and Watanabe 21 .…”
Section: Discussionsupporting
confidence: 88%
“…Sakuramoto et al. indicated that the huge fluctuation of sandfish catch in Akita Prefecture could be explained well by the water temperature in September at 200–300 m depths at 5 km off the Oga Peninsula of Akita Prefecture 18,19 . Noto and Yasuda discussed the population decline of the Japanese sardine and indicated that the winter‐spring SST in the Kuroshio Extension is a controlling factor that determines the strength of the year‐class 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Sakuramoto et al (2001) stated that the 3-year fishing closure off Akita Prefecture appeared to be related to NSJ catch recovery in Akita Prefecture, based on a simulation using the NSJ coastal catch model, although environmental conditions were unfavorable during the fishing moratorium. Our simulation indicated that the biomass in 1991 prior to the fishing moratorium was at least 5Â the actual biomass in 1991 when harvesting was regulated in the 1970s-1980s.…”
Section: Management Implicationsmentioning
confidence: 99%
“…It is useful for developing a catch forecasting model in order to manage snow crab populations. Sakuramoto et al 10 . discussed the fluctuation in sandfish catch by using catch forecasting models incorporating environmental factors.…”
Section: Introductionmentioning
confidence: 99%